Rancang Bangun Sistem Informasi Rekam Medis (Studi Kasus: Klinik PKU Muhammadiyah Gandrungmangu) - Fathan Asyhari; Aridhanyati Arifin (UM Purwokerto Press, 2021)
Health Services at the PKU Muhammadiyah Gandrungmangu Clinic have not made much use of information technology. Documentation of patient medical records still uses a manual recording system, causing various obstacles; for example, officers often find the same medical record number and difficulties making reports. Thus, creating a medical record information system is necessary to help manage medical record data electronically. The system was developed using the prototyping method. This system has several features: medical record management, user management, reporting system, input checking feature for vital sign results, uploading feature for supporting examination results, and patient queuing system for each poly. The results of the user convenience test using the SEQ method obtained an average value of 6 and 7. The usability test results using the SUS method also got a good response from the questionnaire questions given to the respondents, which got a total score of 90.6, meaning that the system has an excellent usability level.